2021
DOI: 10.4049/immunohorizons.2100001
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Transactivates CD8+ T Lymphocytes upon Acute Sterile Tissue Injury

Abstract: Acute major tissue injury induces immune dysregulation that is characterized by the development of systemic sterile inflammation and an increased risk for opportunistic infections. Although the contribution of the innate immune system has been examined in detail, research on the impact of acute sterile tissue damage on the T cell compartment remains limited. In the current study, we used a clinically relevant mouse model for traumatic skeletal muscle injury to investigate the impact of sterile tissue damage on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Our observations indicated that combining allogenic splenocytes with LPS as an adjuvant resulted in a synergistic effect leading to an increased number of CD8+ CD69+ CD25+ T cells. As CD8+ T cells are known to express TLR4 and react to markers of sterile inflammation such as IL-12, we next investigated whether TAK-242 directly inhibits CD8+ T cell activation [ 29 ]. Upon stimulation with CD3/CD28 antibody-coated beads, we noted a dose-dependent decrease in CD8+ T cell activation, as well as proliferation in the presence of TAK-242 that was not affected by inactive analog, MAP84 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our observations indicated that combining allogenic splenocytes with LPS as an adjuvant resulted in a synergistic effect leading to an increased number of CD8+ CD69+ CD25+ T cells. As CD8+ T cells are known to express TLR4 and react to markers of sterile inflammation such as IL-12, we next investigated whether TAK-242 directly inhibits CD8+ T cell activation [ 29 ]. Upon stimulation with CD3/CD28 antibody-coated beads, we noted a dose-dependent decrease in CD8+ T cell activation, as well as proliferation in the presence of TAK-242 that was not affected by inactive analog, MAP84 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%